Difficulties Faced by Science Teachers in Selected Public Schools in Kuwait: A Descriptive Study - Al-Kandari, Ebrahim Abdullah; Ramdane, Tahraoui; Nordin, Mohamad Sahari (IIUM Press, 2019)
This study examined the difficulties experienced by science teachers in selected public secondary schools in the Mubarak Al-Kabeer Governorate in Kuwait. The difficulties they encountered were examined under four aspects: curriculum objectives, student assessment, school management, and science laboratories. Ten schools were randomly selected from a population of 22 schools in the governorate. From the ten schools, seventy-seven science teachers (N = 77) responded to a self-developed questionnaire in Arabic on science teaching difficulties. The questionnaire asked 20 items on the four aspects of science teaching difficulties. Data on the difficulties were summarized as frequencies, percentages, means and standard deviations, while gender differences were determined using chi-squares. The results indicated that both male and female science teachers encountered difficulties with the science curriculum objectives in that they are not clear and do not encompass the important learning domains, i.e. the cognitive, affective, and psychomotor domains. Teachers also found the objectives to lack a systematic order that should range from the lowest to the highest. In regard to assessment, teachers experienced difficulties caused by inconsistent and non-standardized practices, as well as by the lack of alignment between curriculum objectives and assessment practices. Authoritarianism and inflexibility in the school management, and the lack of opportunities for professional growth posed further difficulties for teachers. As for science laboratories, a majority of science teachers reported that they lack good equipment, are located in unsafe places, and do not meet safety standards. No significant gender differences were detected in the teachers' perceptions of difficulties, which was taken to reflect the reality on the ground. That is, the difficulties faced by the teachers were not a function of gender. Based on the results, the study recommends that the science curriculum objectives be reformulated to cover all learning domains, and a consistent student assessment system that is aligned to the curriculum objectives be applied. Outdated and negative school management styles must also be replaced by a democratic style that is positive and motivating.